Environmental Predictors of Undernutrition Among Under-5 Children at Dabat District Health Facilities, Northwest Ethiopia, 2023 - Mihret Melese; Dereje Esubalew; Asmamaw Malede; Tsegaye Adane Birhan; Jember Azanaw (SAGE Publishing, 2024)
Background: In Ethiopia, undernutrition remains a significant public health concern throughout the year due to persistent household food insecurit. The intensifying conflict in the Dabat district, involving the Ethiopian government and the Tigray Liberation Front, has increased the threat of undernutrition among under-5 children. The cessation of humanitarian aid has worsened food insecurity, increasing the vulnerability of the children in the region. However,there was no data showing the prevalence and environmental pridictors of undernutrition in the Dabat district, northwestern Ethiopia. Therefore, the objective of this study was to determine the prevalence of undernutrition and identify environmental pridictors in this study setting. Methods: This institutional-based cross-sectional study was conducted from January to March 2023. A total of 400 under-5 children were included in this study using systematic random sampling techniques with a 100% response rate. The study included all under-5 children who visited healthcare facilities during the data collection period. However, it excluded children under-5 who had physical deformities, were critically ill, or had congenital abnormalities or known chronic diseases such as HIV/AIDS, tuberculosis, or chronic heart diseases. Binary logistic regression was used to determine environmental predictors of undernutrition, with statistical significance at a P -value of ⩽.05. Results: The overall prevalence of undernutrition was found to be 12% (95% CI: 8.72-21.5). Among those affected, 32.8% (95% CI: 21.5-39.8) were stunted, 37.9% (95% CI: 28.8-47.50) were underweight, and 29.3% (95% CI: 21.3-29.7) were wasted. The environmental predictors of undernutrition were latrine use, recent diarrhea episodes, mothers' occupation and place of residence, water treatment before consumption, water sources and storage, water extraction methods, and mothers' handwashing habits. Conclusions and recommendations: The study found a higher prevalence of undernutrition among under-5 children compared to the 2019 Ethiopia Mini Demographic and Health Survey. This study recommended raising awareness about establishing private toilets, promoting water treatment, proper latrine use, and handwashing practices. Training on personal hygiene and economic support for households should also be provided. Healthcare providers should offer quality health services for under-5 children. Further research is needed to explore specific nutrient deficiencies using laboratory methods.